A ceramic product and its preparation process and application

By optimizing the formula of the primitive and glaze of the ceramic tea pet, combined with the process, the problem of insufficient water absorption and breathability of the ceramic tea pet is solved, and the tea fragrance retention and gloss of the ceramic tea pet are improved, which enhances the beauty of the product Sex and durability.

CN119038952BActive Publication Date: 2025-01-03HUNAN HUATAI LIANYE CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523906.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Ceramic tea pets are difficult to retain the tea aroma due to poor water absorption and breathability of the glaze, and their appearance is not easy to change, which lacks the beauty and cultural connotation of traditional tea pets.

Method used

Use a blank made of calcined kaolin, clay, alumina and other materials, and is equipped with a surface glaze containing diatomaceous earth, nano zinc oxide and other components. By optimizing the formulation and process, the water absorption and fracture toughness of ceramic products are improved. and gloss.

Benefits of technology

Ceramic products have a warm and luster, maintain the tea aroma, and have good mechanical properties and durability, which enhances the aesthetics and practical value of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038952B_ABST
    Figure CN119038952B_ABST
Patent Text Reader

Abstract

The present invention discloses a ceramic product and its preparation process and application, and relates to the technical field of ceramics. The present invention provides a ceramic product, which is composed of a bisque and a glaze; the bisque includes: calcined kaolin, clay, alumina, potassium feldspar, sodium feldspar, quartz, calcium titanate, zinc oxide, wollastonite and a pore-forming agent; the slurry of the glaze includes: frit, mullite, diatomaceous earth, calcium carbonate, zirconium silicate, magnesium aluminum spinel and nano zinc oxide. The surface of the ceramic product prepared by the present invention has a warm and moist glossy feeling and has a certain water absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramics, and in particular relates to a ceramic product and a preparation process and application thereof. Background Art

[0002] Tea pets are toys for drinking tea, usually made of purple clay, clay, resin or ceramic. Purple clay tea pets are favored by tea lovers for their unique air permeability and water absorption, and are easy to maintain to a moist luster; however, the maintenance of purple clay tea pets is more complicated and requires regular cleaning and moisturizing. Clay tea pets also have good water absorption and can absorb minerals in tea. As time goes by, their surface will gradually form a smooth and delicate patina effect. However, the color and gloss of clay tea pets are relatively poor. Resin tea pets are a kind of tea pet made of modern materials. They can be made into color-changing tea pets. They will change color immediately when exposed to hot tea and return to their original color after cooling. Although resin tea pets are low in cost, they usually lack traditional beauty and cultural connotations, have poor high temperature resistance and wear resistance, and are easily damaged by physical damage.

[0003] Ceramic tea pets have many advantages. They can be made into a variety of patterns and colors, which are more decorative. Ceramic tea pets are hard, wear-resistant, and not easy to break, making them suitable for long-term use. However, ceramics are difficult to retain the fragrance of tea like purple clay tea pets because of their poor water absorption or air permeability. In addition, purple clay will gradually become patinated after long-term use, so it will become more moist as it is kept, while ceramic tea pets usually do not have such changes in appearance. Therefore, the material of ceramic tea pets needs to have a certain degree of water absorption and air permeability, and the surface can maintain its gloss. Summary of the invention

[0004] The present invention overcomes the above technical problems and provides a ceramic product and a preparation process and application thereof. The ceramic product of the present invention has a warm luster on the surface, has a certain water absorption capacity, and has good fracture toughness.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The present invention provides a ceramic product, which is composed of a biscuit and a glaze;

[0007] The green blank comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 20-35 parts of clay, 11-18 parts of alumina, 3-16 parts of potassium feldspar, 20-28 parts of sodium feldspar, 8-13 parts of quartz, 1-3 parts of calcium titanate, 2-5 parts of zinc oxide, 3-6 parts of wollastonite, and 2-8 parts of pore formers;

[0008] Preferably, the green body comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 25-31 parts of clay, 13-16 parts of alumina, 5-12 parts of potassium feldspar, 22.5-26.5 parts of sodium feldspar, 9-12 parts of quartz, 1.5-2.8 parts of calcium titanate, 2.6-4.3 parts of zinc oxide, 3.4-5.7 parts of wollastonite, and 3.9-7.4 parts of a pore former.

[0009] The glaze slurry comprises the following raw materials in parts by weight: 50 parts of frit, 16-25 parts of mullite, 7-13 parts of diatomaceous earth, 5-10 parts of calcium carbonate, 2-4 parts of zirconium silicate, 1-3 parts of magnesium aluminum spinel, and 2-8 parts of nano zinc oxide;

[0010] Preferably, the glaze comprises the following raw materials in parts by weight: 50 parts of frit, 18-23.2 parts of mullite, 8.5-11.9 parts of diatomaceous earth, 6.3-9.4 parts of calcium carbonate, 2.2-3.9 parts of zirconium silicate, 1.3-2.5 parts of magnesium aluminum spinel, and 2.6-7.1 parts of nano zinc oxide.

[0011] In the glaze formula of the present invention, the water absorption of the glaze is improved by adding diatomaceous earth. Nano zinc oxide can quickly reduce the high-temperature viscosity of the glaze at high temperature due to its nano-scale particles and high specific surface area, thereby maintaining the transparency and high gloss of the glaze; in addition, nano zinc oxide also has antibacterial and deodorizing functions. Magnesium aluminum spinel is usually used to improve the transparency of ceramics due to its excellent optical properties and isotropy. In the glaze formula of the present invention, calcium carbonate decomposes into calcium oxide at high temperature and forms a low eutectic with silicon dioxide, while zirconium silicate precipitates microcrystals in the eutectic to increase the gloss of the glaze. Nano zinc oxide has a higher percentage of zinc interstitial and oxygen vacancy, so it can be used as a mineralizer to promote the formation and growth of magnesium aluminum spinel crystals through solid-phase reaction to maintain good gloss.

[0012] The frit includes the following raw materials in percentage by mass: 41-52% silicon dioxide, 18-20% aluminum oxide, 8-15% boron trioxide, 2-3% sodium oxide, 1-3% potassium oxide, 2.5-11% barium oxide, and 0.5-0.7% phosphorus pentoxide;

[0013] Preferably, the frit comprises the following raw materials in percentage by mass: 51.2% silicon dioxide, 19.7% aluminum oxide, 14.6% boron trioxide, 2.6% sodium oxide, 2.2% potassium oxide, 8.3% barium oxide, and 0.6% phosphorus pentoxide.

[0014] In the present invention, the pore-forming agent is sodium bicarbonate or starch.

[0015] In the present invention, the calcined kaolin is of triclinic crystal form.

[0016] In the present invention, the calcined kaolin has a mesh size of 800-1250.

[0017] In the present invention, the particle size of the nano zinc oxide is D50=20~30nm.

[0018] In the present invention, the specific surface area of ​​the nano zinc oxide is 15-25 m 2 / g, preferably 20m 2 / g.

[0019] In the present invention, the porosity of the blank is 4-9%, preferably 5.5-8.2%. The blank has certain pores, and this air permeability helps the tea fragrance to spread and flow, which helps the ceramic product to maintain the tea fragrance.

[0020] In the present invention, the whiteness of the green blank is 90-95, preferably 91-94.

[0021] In the present invention, the water absorption of the glaze is 6-16%, preferably 8.2-14.6%. The water absorption of the glaze can not only improve the touch of the ceramic product, but also after absorbing the tea juice, the surface of the ceramic product will present a layer of warm luster. This characteristic enables the tea pet to better retain the tea fragrance under the nourishment of the tea soup, and also makes the surface of the ceramic product become smoother and more shiny over time.

[0022] In the present invention, the glossiness of the glaze is 10-30°, preferably 16-27°.

[0023] In the present invention, the fracture toughness of the glaze is 4-7 MPa·m 1 / 2 , preferably 4.8~6.3 MPa·m 1 / 2 Among them, the glaze has excellent fracture toughness, which can make the ceramic products have better mechanical properties when facing sudden cooling and heating, so it is not easy to break.

[0024] The present invention also provides a process for preparing the aforementioned ceramic product, comprising the following steps:

[0025] S1. Preparation of green billet:

[0026] S1.1. The raw materials for preparing the green billet are crushed, finely ground, and sieved through a 280-300 mesh sieve to obtain a green billet powder;

[0027] S1.2. Then add water to the green powder, knead the clay, age it, and shape it to obtain a wet green powder;

[0028] S1.3. After drying the wet billet, biscuit calcining is performed at 800-900°C for 10-20h to obtain a billet;

[0029] S2. Preparation of glaze slurry:

[0030] S2.1. Grind and sieve the raw materials for preparing the glaze to obtain a mixture;

[0031] S2.2. Add water to the mixture to prepare a slurry with a solid content of 48-55%;

[0032] S3. Glazing sintering:

[0033] S3.1. After the biscuit is polished, the slurry is sprayed on the surface of the biscuit, the thickness of the glaze is 1~3mm, and a semi-finished product is obtained;

[0034] S3.1. Sinter the semi-finished product at 1050~1300℃ for 6~15h, cool it to room temperature, and obtain a ceramic product; the cooling rate is controlled at -1~-3℃ / min.

[0035] In S1, the aging temperature is 25-30°C.

[0036] In S1, the aging time is 3 to 7 days.

[0037] In S2, the mesh size of the sieving is 300-325 meshes.

[0038] In S2, the solid content of the slurry is 50-55%.

[0039] In S3, the thickness of the sprayed glaze is 2-2.8 mm.

[0040] In S3, after cooling to room temperature, it is necessary to wait for 2 to 3 hours before opening the kiln.

[0041] In S3, the surface roughness of the green blank after grinding is 0.2-0.5 μm, preferably 0.35-0.44 μm.

[0042] In S3, the heating rate before sintering is 10-20°C / h.

[0043] In S3, the sintering temperature is 1050-1200° C., and the sintering time is 8-10 hours.

[0044] In S3, the cooling speed is controlled at -1 to -3°C / min. If the cooling speed is too fast, the residual stress inside the ceramic product will increase, and this residual stress will increase the brittleness of the material, thereby reducing its fracture toughness.

[0045] The ceramic product as mentioned above, or the application of the preparation process of the ceramic product as mentioned above in tea pet crafts.

[0046] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] 1. The optimization of the blank formula improves its whiteness, which provides a basis for the glossiness of the glaze. At the same time, the blank also has a good porosity, which helps the ceramic products to maintain the aroma of tea and enhance the practical value and cultural heritage of tea pets;

[0049] 2. The water absorption of the glaze is 6~16%, and in some preferred embodiments it is 8.2~14.6%; appropriate water absorption can ensure the moist feeling of the glaze, but will not absorb too much water to affect the use. The glossiness of the glaze is 10~30°, and in some preferred embodiments it is 16~27°, ensuring that the glaze has a warm gloss. The fracture toughness of the glaze is 4~7 MPa·m 1 / 2 , in some preferred embodiments, 4.8~6.3 MPa·m 1 / 2 To ensure that the glaze has good crack resistance.

[0050] 3. By strictly controlling the preparation process, the ceramic product of the present invention not only has a more excellent appearance, but also has good mechanical properties, which significantly improves the durability and aesthetics of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is an appearance diagram of the ceramic product of Example 1.

[0052] Figure 2 This is an apparent diagram of the ceramic product of Example 2. DETAILED DESCRIPTION

[0053] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0054] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0055] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0058] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0060] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] The calcined kaolin (triclinic crystalline, D50 = 0.5 ~ 10 μm, specific surface area 10m 2 / g) was purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd.; nano zinc oxide (purity> 95%, D50 = 10 ~ 30nm, specific surface area of ​​20m 2 / g) was purchased from Darcinon Nanotechnology (Changzhou) Co., Ltd.; the particle size of zinc oxide was D50 = 20~40μm. Wollastonite was purchased from Jiangxi Aote Technology Co., Ltd.; mullite was purchased from Shandong Ansheng New Materials Co., Ltd.; diatomite was purchased from Shijiazhuang Tianxu Environmental Protection Technology Co., Ltd.; and magnesium aluminum spinel was purchased from Henan Fengrun Metallurgical Materials Co., Ltd.

[0062] The composition of the frit is 51.2% silicon dioxide, 19.7% aluminum oxide, 14.6% boron trioxide, 2.6% sodium oxide, 2.2% potassium oxide, 8.3% barium oxide, 0.6% phosphorus pentoxide, and the remainder is unavoidable impurities.

[0063] The porosity test method of the green blanks in the following examples and comparative examples refers to GB / T 25995.

[0064] Example 1

[0065] 1. Ceramic products of this embodiment:

[0066] It consists of a blank and a glaze.

[0067] The green body comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 26 parts of clay, 15 parts of alumina, 6.7 parts of potassium feldspar, 26.5 parts of sodium feldspar, 9.7 parts of quartz, 1.5 parts of calcium titanate, 3.6 parts of zinc oxide, 5.1 parts of wollastonite, and 5.5 parts of a pore former (starch).

[0068] The whiteness of the blank of this embodiment is 95, and the porosity of the blank is 8.2%.

[0069] The slurry of the glaze includes the following raw materials in parts by weight: 50 parts of frit, 19.3 parts of mullite, 9.8 parts of diatomaceous earth, 8.7 parts of calcium carbonate, 2.8 parts of zirconium silicate, 1.7 parts of magnesium aluminum spinel, and 7.1 parts of nano zinc oxide.

[0070] The ceramic product prepared in this embodiment has the following appearance: Figure 1 .

[0071] 2. Preparation method of ceramic products:

[0072] S1. Preparation of green billet:

[0073] S1.1. The raw materials for preparing the green billet are crushed, finely ground, and sieved through a 300-mesh sieve to obtain a green billet powder;

[0074] S1.2. Add water to the green powder and knead it into a mud, age it at 28°C for 5 days, and shape it to obtain a wet green body;

[0075] S1.3. After drying the wet billet, biscuit was calcined at 850°C for 12h to obtain a billet;

[0076] S2. Preparation of glaze slurry:

[0077] S2.1. The raw materials for preparing the glaze are ground and passed through a 325-mesh sieve to obtain a mixture;

[0078] S2.2. Add water to the mixture to prepare a slurry with a solid content of 53%;

[0079] S3. Glazing sintering:

[0080] S3.1. The biscuit is polished to a surface roughness of 0.39 μm, and the slurry is sprayed on the surface of the biscuit to a thickness of 0.22 mm to obtain a semi-finished product;

[0081] S3.1. Heat the semi-finished product at a heating rate of 15℃ / h, sinter it at 1200℃ for 8h, set the cooling rate to -2.5℃ / min, cool it to room temperature (25℃), wait for 3h before opening the kiln to obtain a ceramic product.

[0082] Example 2

[0083] The difference between this embodiment and embodiment 1 is that:

[0084] 1. Ceramic products of this embodiment:

[0085] The green body comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 30 parts of clay, 13.8 parts of alumina, 9.9 parts of potassium feldspar, 23.4 parts of sodium feldspar, 11.6 parts of quartz, 2.8 parts of calcium titanate, 4.1 parts of zinc oxide, 5.6 parts of wollastonite, and 5.2 parts of a pore former (sodium bicarbonate).

[0086] The whiteness of the green body of this embodiment is 94, and the porosity of the green body is 6.7%.

[0087] The glaze slurry includes the following raw materials in parts by weight: 50 parts of frit, 21.4 parts of mullite, 9.3 parts of diatomaceous earth, 6.8 parts of calcium carbonate, 3.4 parts of zirconium silicate, 2.2 parts of magnesium aluminum spinel, and 4.2 parts of nano zinc oxide.

[0088] The ceramic product prepared in this embodiment has the following appearance: Figure 2 .

[0089] Example 3

[0090] The difference between this embodiment and embodiment 1 is that:

[0091] 2. Preparation method of ceramic products:

[0092] S1.2. Add water to the green powder and knead it, then age it at 30°C for 6 days and shape it to obtain a wet green body;

[0093] S1.3. After drying the wet blank, biscuit calcining was performed at 800°C for 15h to obtain a blank;

[0094] The whiteness of the green body is 90, and the porosity of the green body is 5.5%.

[0095] Example 4

[0096] The difference between this embodiment and embodiment 1 is that:

[0097] 2. Preparation method of ceramic products:

[0098] S2. Preparation of glaze slurry:

[0099] S2.1. The raw materials for preparing the glaze are ground and sieved through a 300-mesh sieve to obtain a mixture;

[0100] S2.2. Add water to the mixture to prepare a slurry with a solid content of 51%;

[0101] S3. Glazing sintering:

[0102] S3.1. Grind the blank to a surface roughness of 0.42 μm, spray the slurry on the surface of the blank to a thickness of 0.26 mm, and obtain a semi-finished product.

[0103] Example 5

[0104] The difference between this embodiment and embodiment 1 is that:

[0105] S3.1. Heat the semi-finished product at a heating rate of 20℃ / h, sinter it at 1100℃ for 10h, set the cooling rate to -3.0℃ / min, cool it to room temperature and then open the kiln after 3h to obtain a ceramic product.

[0106] Comparative Example 1

[0107] The difference between this comparative example and Example 1 is:

[0108] 1. Ceramic products of this comparative example:

[0109] The green body comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 26 parts of clay, 15 parts of alumina, 6.7 parts of potassium feldspar, 26.5 parts of sodium feldspar, 9.7 parts of quartz, 1.5 parts of calcium titanate, 3.6 parts of zinc oxide and 5.1 parts of wollastonite.

[0110] The whiteness of the green body is 88, and the porosity of the green body is 1.7%.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 1 is:

[0113] 1. Ceramic products of this comparative example:

[0114] The slurry of the glaze comprises the following raw materials in parts by weight: 50 parts of frit, 18-23.2 parts of mullite, 5.6 parts of diatomaceous earth, 8.8 parts of calcium carbonate, 3.1 parts of zirconium silicate, and 0.8 parts of nano zinc oxide.

[0115] Comparative Example 3

[0116] The difference between this comparative example and Example 1 is:

[0117] 2. Preparation method of ceramic products:

[0118] S3.1. Heat the semi-finished product at a heating rate of 15°C / h, sinter it at 1200°C for 8h, set the speed to -5°C / min, and open the kiln after cooling to room temperature to obtain a ceramic product.

[0119] Comparative Example 4

[0120] The difference between this comparative example and Example 2 is that:

[0121] The slurry of the glaze includes the following raw materials in parts by weight: 50 parts of frit, 21.4 parts of mullite, 9.3 parts of diatomaceous earth, 0.8 parts of calcium carbonate, 3.4 parts of zirconium silicate, 2.2 parts of magnesium aluminum spinel, and 4.2 parts of nano zinc oxide.

[0122] Comparative Example 5

[0123] The difference between this comparative example and Example 2 is that:

[0124] The glaze slurry includes the following raw materials in parts by weight: 50 parts of frit, 21.4 parts of mullite, 9.3 parts of diatomaceous earth, 6.8 parts of calcium carbonate, 3.4 parts of zirconium silicate, 2.2 parts of magnesium aluminum spinel, and 1.0 part of nano zinc oxide.

[0125] Comparative Example 6

[0126] The difference between this comparative example and Example 2 is that:

[0127] The glaze slurry includes the following raw materials in parts by weight: 50 parts of frit, 21.4 parts of mullite, 9.3 parts of diatomaceous earth, 6.8 parts of calcium carbonate, 3.4 parts of zirconium silicate, 2.2 parts of magnesium aluminum spinel, and 4.2 parts of zinc oxide (nano zinc oxide is not used).

[0128] Test Case

[0129] The glazes in the ceramic products prepared in the above embodiments and comparative examples were tested for their effects. The glaze slurry used in embodiment 3 and comparative example 1 was the same, and no repeated tests were performed; the glaze gloss test method of the other embodiments and comparative examples was prepared according to GB / T 3295, the fracture toughness test method was according to GB / T 23806, and the water absorption test method was according to GB / T 3299. The test results are shown in Table 1.

[0130] ;

[0131] It can be seen from the above embodiments and comparative examples in combination with Table 1 that in comparative example 1, no pore-forming agent was added to the raw materials for preparing the biscuit, resulting in a low porosity of the biscuit. In comparative example 2, due to insufficient diatomite content, the water absorption of the glaze was poor; at the same time, the content of nano zinc oxide was also low, which affected the gloss of the glaze. In comparative example 3, the cooling speed was too fast, resulting in too fast stress release of the glaze, thereby reducing the fracture toughness of the glaze.

[0132] The main difference between Comparative Example 4 and Example 2 is the content of calcium carbonate. Since the content of calcium carbonate in Comparative Example 4 is relatively low, it is not conducive to the precipitation of zirconium silicate, which in turn affects the glossiness of the glaze. In addition, the lower calcium carbonate content also leads to a slight decrease in fracture toughness.

[0133] The difference between Comparative Example 5 and Example 2 is the content of nano zinc oxide. The content of nano zinc oxide in Comparative Example 5 is relatively low, which limits the secondary spinelization degree of magnesium aluminum spinel, thereby affecting the glossiness of the glaze. At the same time, since the secondary spinelization of nano zinc oxide and magnesium aluminum spinel has a positive effect on improving fracture toughness, the fracture toughness of Comparative Example 5 is also significantly reduced.

[0134] The difference between Comparative Example 6 and Example 2 is whether nano zinc oxide is used. Comparative Example 6 does not use nano zinc oxide, but uses ordinary zinc oxide, which has a poor secondary spinelization effect on magnesium aluminum spinel, far less effective than nano zinc oxide as a mineralizer. This results in insufficient crystallization, poor glaze color and transparency, and a slightly frosted texture. Similarly, due to the lack of the positive effect of nano zinc oxide, the fracture toughness of Comparative Example 6 is also greatly reduced.

[0135] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A ceramic product, characterized in that: It is composed of bisque and glaze; The green blank comprises the following raw materials in parts by weight: 50 parts of calcined kaolin, 20-35 parts of clay, 11-18 parts of alumina, 3-16 parts of potassium feldspar, 20-28 parts of sodium feldspar, 8-13 parts of quartz, 1-3 parts of calcium titanate, 2-5 parts of zinc oxide, 3-6 parts of wollastonite, and 2-8 parts of pore formers; The glaze slurry comprises the following raw materials in parts by weight: 50 parts of frit, 16-25 parts of mullite, 7-13 parts of diatomaceous earth, 5-10 parts of calcium carbonate, 2-4 parts of zirconium silicate, 1-3 parts of magnesium aluminum spinel, and 2-8 parts of nano zinc oxide; The frit includes the following raw materials in percentage by mass: 41-52% silicon dioxide, 18-20% aluminum oxide, 8-15% boron trioxide, 2-3% sodium oxide, 1-3% potassium oxide, 2.5-11% barium oxide, and 0.5-0.7% phosphorus pentoxide.

2. The ceramic product according to claim 1, characterized in that Meet at least one of the following conditions ①~⑤: ① The pore-forming agent is sodium bicarbonate or starch; ② The calcined kaolin is triclinic; ③ The calcined kaolin is 800-1250 mesh; ④ The particle size of the nano zinc oxide is D50=20~30nm; ⑤ The specific surface area of ​​the nano zinc oxide is 15~25m 2 / g.

3. The ceramic product according to claim 1, characterized in that Meet at least one of the following conditions ①~②: ① The porosity of the green blank is 4-9%; ② The whiteness of the green billet is 90-95.

4. The ceramic product according to claim 1, characterized in that Meet at least one of the following conditions ①~③: ① The water absorption of the glaze is 6-16%; ② The glossiness of the glaze is 10~30°; ③ The fracture toughness of the glaze is 4~7 MPa·m 1 / 2 .

5. The process for preparing a ceramic product according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparation of green billet: S1.

1. The raw materials for preparing the green billet are crushed, finely ground, and sieved through a 280-300 mesh sieve to obtain a green billet powder; S1.

2. Then add water to the green powder, knead the clay, age it, and shape it to obtain a wet green; S1.

3. After drying the wet billet, biscuit calcining is performed at 800-900°C for 10-20h to obtain a billet; S2. Preparation of glaze slurry: S2.

1. Grind and sieve the raw materials for preparing the glaze to obtain a mixture; S2.

2. Add water to the mixture to prepare a slurry with a solid content of 48-55%; S3. Glazing sintering: S3.

1. After the biscuit is polished, the slurry is sprayed on the surface of the biscuit, the thickness of the glaze is 1~3mm, and a semi-finished product is obtained; S3.

1. Sinter the semi-finished product at 1050~1300℃ for 6~15h, cool it to room temperature, and obtain a ceramic product; the cooling rate is controlled at -1~-3℃ / min.

6. The process for preparing a ceramic product according to claim 5, characterized in that: Meet at least one of the following conditions ①~②: ① The aging temperature is 25-30°C; ②The aging time is 3 to 7 days.

7. The process for preparing a ceramic product according to claim 5, characterized in that: The mesh number of the sieving is 300-325 meshes.

8. The process for preparing a ceramic product according to claim 5, characterized in that: Meet at least one of the following conditions ①~②: ① After cooling to room temperature, it is necessary to wait for 2 to 3 hours before opening the kiln; ② The surface roughness of the green blank after grinding is 0.2~0.5μm.

9. The process for preparing a ceramic product according to claim 5, characterized in that: Meet at least one of the following conditions ①~②: ① The heating rate before sintering is 10-20 ℃ / h; ② The sintering temperature is 1050-1200°C, and the sintering time is 8-10h.

10. Use of the ceramic product according to any one of claims 1 to 4 or the preparation process of the ceramic product according to any one of claims 5 to 9 in tea pet crafts.